Factors associated with the use of deworming drugs during pregnancy in Tanzania; an analysis from the 2015-16 Tanzanian HIV and malaria indicators survey - Vicent Bankanie; Fabiola Vincent Moshi (BMC, 2022)
Abstract Background The use of deworming drugs is one of the important antenatal strategies in preventing anaemia in pregnancy. Little is known about the factors associated with the use of deworming drugs, which accounts for the aim of this study. Method The study used data from the 2015-16 Tanzania HIV Demographic and Health Survey and Malaria Indicators Survey (2015-16 TDHS-MIS). A total of 6924 women of active reproductive age from 15 to 49 were included in the analysis. Both univariate and multiple logistic regression analyses were used. Results The majority of interviewed women 3864(60.1%) took deworming drugs. In a weighed multiple logistic regression, women residing in urban areas reported greater use of deworming drugs than women residing in rural areas [AOR = 1.73, p = 0.01, 95% CI (1.26-2.38)]. In the four areas of residence, compared to women residing in mainland rural areas, women residing in mainland urban areas and Pemba islands reported greater use of deworming drugs [mainland urban (AOR = 2.56 p < 0.001,95% CI(1.78-3.75), and Pemba Island (AOR = 1.18, p < 0.001, 95% CI(1.17-1.20)]. However, women residing in Zanzibar Island (Unguja) were less likely to use deworming drugs compared to women in mainland rural women (AOR = 0.5, p < 0.001, 95% CI (0.45-0.55). Similarly, compared to women under 20 years of age, women between 20 to 34 years reported significantly greater use of deworming drugs [20 to 34 years (AOR = 1.30, p = 0.03, 95% CI(1.02-1.65). Likewise, greater use of deworming drugs was reported in women with a higher level of education compared to no education [higher education level (AOR = 3.25, p = 0.01,95% CI(1.94-7.92)], rich women compared to poor [rich (AOR = 1.43, p = 0.003, 95% CI (1.13-1.80)] and in women who initiated antenatal care on their first trimester of pregnancy compared to those who initiated later [AOR = 1.37, p < 0.001, 95% CI (1.17-1.61)]. Conclusion Women who were more likely to use the deworming drugs were those residing in urban compared to rural areas, aged between 20 and 34 years, those with a higher level of formal education, wealthier, and women who book the antenatal clinic (ANC) within their first trimester of pregnancy. Considering the outcomes of anaemia in pregnancy, a well-directed effort is needed to improve the use of deworming drugs.